Improvement of Hand Motor Function after Radial Shock Wave Therapy in Chronic Stroke Patients - M. Kamaluddin K; Erna Setiawati; Tanti Ajoe Kesoema (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: The Radial Shock Wave Therapy (RSWT) expected could improve spasticity and hand function in chronic stroke patients. This study aimed to find out the improvement of hand function after RSWT as an additional therapy in chronic stroke patients. Methods: Design study was a randomized controlled trial, in December 2018. The patients were assigned randomly to the experimental group (Infrared, Stretching, and RSWT) and control group (Infrared and Stretching) for six weeks. Hand motor function was measured using Fugl-Meyer Motor Assesment (FMA) before and after intervention. Results: The median values of wrist FMA scores in the experimental and control group before and after intervention were 2 vs 5 (p=0.001) and 3 vs 4 (p<0.001) respectively. The median values of hand FMA scores in the experimental and control group before and intervention were 4 vs 6 (p=0,.001) and 4 vs 5 (p<0.001). However, the delta between before and after intervention was higher in experimental group. Conclusion: The improvement of wrist and hand FMA scores after added treatment by RSWT was tend to higher.Keywords: Spasticity, Hand Function, Stroke, Radial Shock Therapy, Fugl-Meyer Motor Assesment